Rhabdomyolysis induced acute kidney injury following physical exertion and severe hypercalcaemia in recovery phase-a case report (Journal of Armed Forces Medical College, Bangladesh, 2015)
In military profession, acute kidney injury (AKI) due to rhabdomyolysis is not uncommon because of its nature of job. This life threatening condition needs early aggressive management in a specialized centre to restore normal renal function. Here we report a case of rhabdomyolysis due to physical exertion who developed acute kidney injury and required haemodialysis. Patient developed hypercalcaemia in his recovery phase which was successfully managed. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21849 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013